THE EFFECT OF AUTHORIZED CAPITAL AND CORPORATE INVENTORIES ON TOTAL REVENUE IN PLANTATION COMPANIES LISTED ON IDX - Romli, Ombi; Khodijah, Ina (International Journal of Multidisciplinary Research and Literature, 2022)
Some of the problems found in this study include; (1) The total revenue of the plantation sub-sector companies is in a downward trend, (2) Most of the plantation sub-sector companies also include authorized capital, which is below 1 billion rupiahs which have the potential to reduce investor perceptions (3 ) The value of corporate inventories still tends to be in the high category. This study aims to analyze the effect of authorized capital and corporate inventories on the total revenue of plantation companies listed on the Stock Exchange for the 2016-2020 period. The research method used in this study is a causal associative method with a quantitative approach. Sampling was done using purposive sampling obtained from 16 plantation companies listed on the Stock Exchange as research samples. The results of partial hypothesis testing show that the authorized capital variable (X1) does not affect total revenue (Y). TQ12 this is evidenced by the value of tcount < ttableR (0.555 < 1.99085), corporate inventories variable (X2) has an influence on total revenue (Y) as evidenced by the value of tcount > ttableR (18.874 > 1.99085) and simultaneous hypothesis testing shows that the authorized capital variable (X1) and corporate inventories (X2) have no effect on total revenue (Y) as evidenced by the value of Fcount < Ftable (183.80 > 3.12). Based on the analysis above, it can conclude that partially authorized capital does not affect total revenue during the inventory variable affects total revenue, and simultaneously, assigned capital and inventory variables influence total revenue